Associations between local COVID-19 policies and anxiety in the USA: a longitudinal digital cohort study - Jeffrey E Olgin; Gregory M Marcus; Rita Hamad; John Kornak; Carmen R Isasi; Ana Sanchez-Birkhead; Mark Pletcher; Soo Park; Natasha Williams; Thomas Carton; Aaron E Cozen; Madelaine Faulkner Modrow; et al. (BMJ Public Health)
Introduction A lack of coordinated federal guidance led to substantial heterogeneity in local COVID-19 policies across US states and counties. Local government policies may have contributed to increases in anxiety and mental health disparities during the COVID-19 pandemic.Methods We analysed associations between composite policy scores for containment and closure, public health or economic support from the US COVID-19 County Policy Database and self-reported anxiety scores (Generalised Anxiety Disorder-7) from COVID-19 Citizen Science participants between 22 April 2020 and 31 December 2021.Results In 188 976 surveys from 36 711 participants in 100 counties across 28 states, associations between anxiety and containment and closure policy differed by employment (p<0.0001), with elevated anxiety under maximal policy for people working in hospitality and food services (+1.05 vs no policy; 95% CI: 0.45, 1.64) or arts and entertainment (+0.56; 95% CI 0.15, 0.97) and lower anxiety for people working in healthcare (−0.43; 95% CI −0.66 to –0.20) after adjusting for calendar time, county-specific effects and COVID-19 case rates and death rates. For public health policy, associations differed by race and ethnicity (p=0.0016), with elevated anxiety under maximal policy among participants identifying as non-Hispanic Black (+1.71; 95% CI 0.26, 3.16) or non-Hispanic Asian (+0.74; 95% CI 0.05, 1.43) and lower anxiety among Hispanic participants (−0.63, 95% CI −1.26 to –0.006). Associations with public health policy also differed by gender (p<0.0001), with higher anxiety scores under maximal policy for male participants (+0.42, 95% CI 0.09, 0.75) and lower anxiety for female participants (−0.40, 95% CI −0.67 to –0.13). There were no significant differential associations between economic support policy and sociodemographic subgroups.Conclusions Associations between local COVID-19 policies and anxiety varied substantially by sociodemographic characteristics. More comprehensive containment policies were associated with elevated anxiety among people working in strongly affected sectors, and more comprehensive public health policies were associated with elevated anxiety among people vulnerable to racial discrimination.